FIRST CONFIRMED SARS-COV-2 DELTA VARIANT IN SERBIA - Opancina, Valentina D; Lara Bohoyo, Jorge Juan; Alcazar Perez, Christina; Todorovic, Ana; Opancina, Miljan; Radojevic Marjanovic, Ruzica; Vojinovic, Radisa (Medicinski časopis, 2021)
Severe acute respiratory syndrome coronavirus 2 is a Betacoronavirus of 2B group that belongs to the family of Coronaviridae. Delta variant, which emerged in the Indian State of Maharashtra in December 2020, is nowadays the variant of concern most widespread and it consists on 3 subtypes, B.1.617.1, B.1.617.2, B.1.617.3. The transmission rate of Delta variant is 50%-60% higher than the Alpha variant and this variant is what currently concerns the world population.In this paper, we present the case of a firste registered patient with Delta variant of COVID-19 in Serbia.
Keywords: COVID-19; SARS-CoV-2; Delta variant.